A conceptual framework for facilitating optimal functioning by survivors of cerebro-vascular accidents and their caregivers at home in Oshana Region, Namibia - Kuugongelwa, Suama; Small, Louis (International Journal of Advanced Nursing Studies, 2016)
Providing care for the survivors of a cerebro-vascular accident in home settings is an increasingly common practice. Accordingly, a conceptual framework was developed with the aim of establishing guidelines for the implementation of a support programme to enable survivors and their caregivers to function optimally at home. The framework involves the attributes of the agent (lecturer as a facilitator), the recipients (survivors and caregivers), the context (the home setting), the procedures for enabling optimal functioning and, finally, the terminus, which is defined at optimal functioning for both the survivors and their caregivers.